Phenotypic Variability of an Inherited Pathogenic Variant in CIC Gene: A New Case Report in Two-Generation Family and Literature Review - Kishnani, Sujata; Riley, Kacie; Mikati, Mohamad A.; Jiang, Yong-hui (Journal of Pediatric Neurology, 2020)
CIC encodes capicua protein, a transcriptional repressor that is highly expressed in developing brains. A previous study reported pathogenic mutations in the CIC gene in five individuals with significant neurodevelopmental disorders of intellectual disability, epilepsy, and autism spectrum disorder. All these mutations are either de novo or likely due to germline mosaicism. Here we reported a pathogenic mutation (c.2694dupC; p.K899Qfs X32: NM_015125) in the CIC gene in three members of a two-generation family presenting with neurodevelopmental impairment but has significant phenotypic variability. Interestingly, loss of function variants of somatic origin are frequently found in cancers of brain and other organs. We summarized germline and somatic pathogenic or loss of function variants in CIC gene in public genome databases through in silico analysis and published literature. Our findings provided further evidence to support the review of haploinsufficiency of CIC in neurodevelopmental disorder, in addition to suggesting a strong modifier effect for the CIC mutations.
Keywords: CIC; capicua; absence seizure; autism spectrum disorder